Implementasi Kurikulum 2013 Mata Pelajaran Pendidikan Agama Islam di SMP PGRI Tebedak - Muhdalia Muhdalia; Lili Rahmawati; Romizah Romizah; M. Syarif Al Akbar; Dwi Noviani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to analyze the implementation of the 2013 Curriculum in Islamic Religious Education (PAI) subjects at the Junior High School (SMP) level. The 2013 curriculum, introduced by the Indonesian government, prioritizes a competency-based approach with a focus on developing students' attitudes, knowledge and skills holistically. In the context of Islamic Religious Education, the implementation of this curriculum is expected to shape the character and personality of religious students and develop their understanding of Islamic teachings in a comprehensive manner. The research method used is descriptive qualitative with a case study approach in several junior high schools in Indonesia. Data collection was carried out through observation, in-depth interviews with PAI teachers, and analysis of documents related to the implementation of the 2013 Curriculum. The research results showed that the implementation of the 2013 Curriculum in PAI subjects faced several challenges, including limited resources, teacher readiness, and diversity in student abilities. However, several schools have demonstrated success in adapting this curriculum well, especially through ongoing teacher training and the development of creative and contextual learning materials. Other findings from this research indicate that the use of active and collaborative learning methods, such as group discussions and projects, can increase student participation and understanding in PAI lessons. Apart from that, the integration of information and communication technology (ICT) in the learning process also contributes positively to the effectiveness of implementing this curriculum. Overall, this research concludes that although there are various challenges in implementing the 2013 Curriculum for Islamic Religious Education subjects in junior high schools, efforts to increase teacher competency and use innovative learning methods can optimize student learning outcomes. Recommendations are given to the government and education stakeholders to continue to support teacher training programs, develop relevant teaching materials, and improve educational facilities and infrastructure to support the successful implementation of the 2013 Curriculum.